046 Efficacy and safety of intravenous immunoglobulin (IVIG) IGPRO10 in chronic inflammatory demyelinating polyneuropathy (CIDP). Issue 6 (24th May 2018) - Sabet, Arman; Mielke, Orell; Schaik, Ivo N van; Leger, Jean-Marc; Bril, Vera; Gloven, Nan van; Hartung, Hans Peter; Lewis, Richard A; Sobue, Gen; Lawo, John-Philip; Durn, Billie L; Cornblath, David R; et al.
Abstract : Introduction: We analysed the efficacy and safety of IVIG IgPro10 (CSL Behring) in two CIDP studies: PRIMA and PATH. Methods: PRIMA was a prospective, open-label, single-arm study in 28 CIDP patients (n=13 IVIG-pretreated; n=15 untreated) investigating efficacy and safety of IgPro10 for induction (2 g/kg) and maintenance therapy (1 g/kg every 3 weeks for 21 weeks). This regimen was also used for 207 IVIG-pretreated patients during the 10–13 week pre-randomization phase of the PATH study (before randomization to subcutaneous immunoglobulin maintenance therapy or placebo). Both studies investigated a 1-point decrease in adjusted Inflammatory Neuropathy Cause and Treatment (INCAT) disability score as a response parameter, and evaluated changes in mean grip strength and Medical Research Council (MRC) score. Treatment-emergent adverse events (AEs) were assessed. Results: Response rate was 76.9% (95% confidence interval [CI] 49.7–91.8) in PRIMA (IVIG-pretreated patients) at week 21% and 72.9% (95%CI 66.5–78.5) in PATH at week 13; median time to first INCAT response was 3.0 and 3.7 weeks, respectively. Median (Q1;Q3) improvements in outcome measures (baseline to last observation) for PRIMA pre-treated patients and PATH, respectively, were: INCAT, −2.0 (-3.0;−1.0) and −1.0 (-2.0;0.0) points; grip strength, 5.0 (-9.0;22.0) and 9.4 (1.3;18.8) kPa; and MRC score, 5.0 (3.0;10.0) and 3.0 (0.0;6.0) points. In the PRIMA safety population (n=28), 108 AEs occurred in 22 (78.6%) patients (0.417/infusion); 284 AEs in 100 (48.3%) patients (0.175/infusion) were reported in the PATH safety population (n=207). Headache was the most frequent AE. Causally related serious AEs in PRIMA and PATH occurred in 2 and 7 patients, respectively. Conclusion: Similar efficacy results of IgPro10 in CIDP were observed in PRIMA and the PATH pre-randomization period. IgPro10 is well tolerated, with clinically meaningful improvement in disability in CIDP patients. Study Support: CSL Behring